2017
DOI: 10.1002/2017gl073904
|View full text |Cite
|
Sign up to set email alerts
|

Joint Sentinel‐1 and SMAP data assimilation to improve soil moisture estimates

Abstract: SMAP (Soil Moisture Active and Passive) radiometer observations at ∼40 km resolution are routinely assimilated into the NASA Catchment Land Surface Model to generate the 9 km SMAP Level‐4 Soil Moisture product. This study demonstrates that adding high‐resolution radar observations from Sentinel‐1 to the SMAP assimilation can increase the spatiotemporal accuracy of soil moisture estimates. Radar observations were assimilated either separately from or simultaneously with radiometer observations. Assimilation imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 38 publications
5
81
0
Order By: Relevance
“…2 of 20 salinity (SMOS) satellites [10] based on L-band passive microwaves can provide high-accuracy global daily SM products [16]. However, coarse-resolution passive microwave SM data cannot reflect the detailed distribution of surface SM; therefore, many researchers have downscaled coarse-resolution passive microwave SM data based on fine-resolution auxiliary data [17][18][19][20][21][22][23].Some downscaling methods are based on active or passive microwave data including downscaling coarse-resolution microwave brightness temperature (TB) data or coarse-resolution SM data based on microwave backscatter data [22,[24][25][26][27][28][29][30], and downscaling low-frequency passive microwave data based on high-frequency passive microwave data [31][32][33]. Active microwave techniques offer higher spatial resolutions than passive microwave techniques.…”
mentioning
confidence: 99%
“…2 of 20 salinity (SMOS) satellites [10] based on L-band passive microwaves can provide high-accuracy global daily SM products [16]. However, coarse-resolution passive microwave SM data cannot reflect the detailed distribution of surface SM; therefore, many researchers have downscaled coarse-resolution passive microwave SM data based on fine-resolution auxiliary data [17][18][19][20][21][22][23].Some downscaling methods are based on active or passive microwave data including downscaling coarse-resolution microwave brightness temperature (TB) data or coarse-resolution SM data based on microwave backscatter data [22,[24][25][26][27][28][29][30], and downscaling low-frequency passive microwave data based on high-frequency passive microwave data [31][32][33]. Active microwave techniques offer higher spatial resolutions than passive microwave techniques.…”
mentioning
confidence: 99%
“…The recent Soil Moisture Active Passive (SMAP) satellite provides global surface SM with generally low errors across different climate regions (Kumar et al, 2018). Numerous studies have evaluated SMAP data with ground-based observations (Chan et al, 2016;Pan et al, 2016) and used SMAP data to improve hydrological and carbon flux simulations (Alvarez-Garreton et al, 2016;He et al, 2017;Kumar et al, 2015;Lievens et al, 2017Lievens et al, , 2015. Recently, Lawston, Santanello, and Kumar (2017) demonstrated that SMAP data can be used to detect seasonal timing and spatial signature of irrigation.…”
Section: 1029/2018gl080870mentioning
confidence: 99%
“…the Advanced SCATterometer, ASCAT; the Soil Moisture and Ocean Salinity, SMOS; and Soil Moisture Active Passive, SMAP). Recent analyses were carried out by assimilating S1 SAR and SMAP radiometer observations within the NASA Catchment Land Surface Model to improve the accuracy of SM estimates (Lievens et al, 2017) and by exploiting a S1-based SM map as input data for an event-based rainfall-runoff model for improving its hydrological simulation (Alexakis et al, 2017). However, to our knowledge, there is a lack of studies dealing with the assimilation of S1-derived SM products within hydrological modelling to improve continuous streamflow simulations and flash flood predictions (preliminary analyses -preparatory to this study -can be found in Cenci, 2016, Cenci et al, 2016b, c, and Cenci et al, 2017a.…”
Section: Introductionmentioning
confidence: 99%